ATRIAL FIBRILLATION AND ATHEROSCLEROSIS OF MAIN ARTERIES: IS THERE ANY CORRELATION? - O. A. Germanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
In article, we observe the changes of main parameters of heart biomechanics and kinetics of main arteries in patients with different types of atrial fibrillation. We describe mechanisms that cause the trauma of mechanical factors on arteries walls in atrial fibrillation with different duration of maximum pause between ventricles contraction. Atrial fibrillation is the additional risk factor of main arteries atherosclerosis. We demonstrated the danger of atrial fibrillation with pauses between ventricles contractions more than 2 seconds from the point of view of appearing and progressing of atherosclerosis.